Improving The Ability To Read Rhythmic Ensembles of A Type Of Music Using The Model Song Media In Class VIII SMP Negeri 3 Teluk Keramat - Rr. Sri Widhi Astuti (Ridwan Institute, 2022)
This class action research (PTK) aims to improve students' rhythmic reading skills in playing similar music ensembles by using model song media in class VII-A SMP Negeri 3 sacred bay sambas west Kalimantan. The study was conducted with two cycles of 35 students. Based on the results of the processing of research data and test results obtained as follows: The results of the pre-observation stage assessment showed students who met the assessment indicator only five out of 33 numbers students, namely: 15.15% of the expected 100%. In cycle 1, students were notified about the assessment indicators, divided groups of students into two groups, prepared teaching materials about notes and silent sign materials and similar musical ensemble materials and students were given an explanation of the meaning of musical ensembles, rhythms, and time signatures. The researcher showed several videos about playing ensembles. Evaluation is carried out individually/individually to play the scores that have been distributed using applause. The average score of the initial Test results is 67.6. The results of the assessment stage of the cycle test stage I students who meet the assessment indicator or reach KKM are 16 students or 48.5%. Students who have not earned the Teaching Completion Criteria are 17, 51.5%. Assessment activities are categorized into two types, namely individual test taking and group testing. The assessment is carried out individually first and then followed by a group assessment. The researcher will call one by one the students who are adjusted to the serial number in the student absent list to play a rhythmic pattern according to the musical instrument they carry. After doing the individual test, then a group test is carried out with the aim of seeing the cohesiveness of students in playing ensemble music. The results of the assessment stage of the cycle II test showed that students who met the assessment indicator or achieved the Minimum Completion Criteria (KKM) were as many as 33 students or 100%. The average score of students' rhythmic reading ability in cycle 2 was 83.3 with the Good category. From the study results, it can be concluded that using model song media can improve the ability to read rhythmically in playing similar music ensembles for students of grade VII-A